Implementación de la interfaz hombre-máquina (hmi) para el medidor de energía multiparámetro sentron pac del laboratorio de Electromecánica de la Universidad Técnica de Cotopaxi Extensión La Maná. - Orbe Peña, Jordy Gabriel (2023)
To create the HMI interface, the problems that arise due to its lack can be observed, where students of the electromechanical engineering career at the Technical University of Cotopaxi La Maná Extension can acquire practical knowledge of the processes carried out in the industry through of an experimental method, in order to improve the teaching and learning process. With this project, the procedures in the design, programming and implementation of the HMI interface are detailed. The development of this project arises from the need to better understand the implementation of the human-machine interface (HMI) for the meter. sentron PAC multiparameter energy test from the electromechanics laboratory of the Technical University of Cotopaxi La Maná Extension. Not having a network data storage system, the need to implement an HMI interface was decided; a Weintek IP8071 screen was used to display the energy parameters measured by the Sentron PAC 3120 in existing three-phase installations in the laboratory. Initially, basic concepts of control system automation are presented, which are HMI interfaces, equipment to occupy types of loads that serve to better understand the advantages obtained when carrying out an operation with power factor correction. It should be noted that all the parameters measured by the sentron PAC 3120 are sent to the HMI screen and stored on a USB, ready for data extraction in different spreadsheets.